Study on effects of soil properties towards corrosion of carbon steel pipeline - Wan Muhammad Azamuddin, Wan Azmi (2014)
Corrosion is one of the most terrifying incidents that engineers does not want on the pipeline, especially when involving billion of dollars losses. Many industries depended on the pipeline for transporting their raw material or products from the places of source to the place of treatment and finally to the consumers. Among the industries that widely used the function of pipeline were oil and gas industries, water treatment and also crude oil industries. Therefore, as the most important part in transportation role, pipeline need to be ensured always in great condition and anything that could cause damages to these railways must be control immediately before unwanted accident happens. Currently, there were report that said pipeline damages was very dangerous to the environment whether to the human being or to the nature. There were some human fatality and body damages of the environment that caused billion of dollars losses. Due to all consequences that would occur in the future as the punishment for the lack of information on the conservation of pipelines, the research based on this problem will be done to find out the cause of buried pipelines damages due to the soil. The research will focus on the soil properties and its effects towards the corrosion of carbon steel pipeline. The parameters that will be the variables in this research are clay content, moisture content, pH value and also particles size of soil. Relationship between these parameters with the corrosion rate will be investigated properly. The pipelines samples will be taken from actual segment and will be buried in different condition of soil based on previous parameters. About 180 samples plates will be buried for at least 5 months to get the real corrosion rate for different type of soil condition. Once a month the retrieval procedure will be done to check the rate of corrosion and also to ensure the soil properties remain stables as been set up. After all the samples had been retrieve from its medium of different soil conditions, the data will be interpreted in form of tables and graph to shows different parameters will get different results. The result from linear regression analysis and also using excel analysis had shown that the pH parameter were could accept the hypothesis of pH condition were the major influence in corrosion rate phenomenon while others had rejected the hypothesis to become the major influence. The ANOVA analysis also shown the correlation coefficient of all the parameters were high but only the pH condition were satisfy the significance value with lower than 0.05. The pH condition, moisture and clay parameter could be study further while the particles size particles does not suitable for further study